1998
DOI: 10.1002/(sici)1521-4095(199810)10:14<1112::aid-adma1112>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Light-Emitting Diodes Based on an Organic-Soluble Poly(p-phenylenevinylene) Derivative Carrying the Electron-Transporting PBD Moiety

Abstract: barrier between the anode and the I p of the HTL is the primary criterion for efficient hole injection. This points to a more complicated relationship between carrier injection than is predicted simply from energy level offset considerations. Other explanations for efficient hole injection are based on the importance of good adhesion between the organic layers and ITO. Defect states at the interface between the organic layer and the electrode have also been shown to be useful for enhancing injection over energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(59 citation statements)
references
References 12 publications
5
54
0
Order By: Relevance
“…There have been several reports on the improvement of p-conjugated polymers such as PPV and polyfluorene by introducing hole-transporting and/or electron-transporting groups to realize highly efficient electroluminescence [9][10][11][12][13][14][15][16][17]. For example, Jin et al reported PPV-based copolymers containing an oxadiazole group with an electron injecting and transporting ability [9].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on the improvement of p-conjugated polymers such as PPV and polyfluorene by introducing hole-transporting and/or electron-transporting groups to realize highly efficient electroluminescence [9][10][11][12][13][14][15][16][17]. For example, Jin et al reported PPV-based copolymers containing an oxadiazole group with an electron injecting and transporting ability [9].…”
Section: Introductionmentioning
confidence: 99%
“…The first reason for the so low QY values is the imbalance of hole/electron injection and transport because the emissive polymer conduct holes are used in preference to electrons [21,22]. Due to the easily trapped excitons and constant nonradiative decay, there is the presence of defects in the polymer, so this is the second reason [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…[16] Their another possible application field is water-soluble biological sensors for the recognition of DNA, proteins, metal ions and small bioanalyses on the foundation of modifications in photoluminescence and UV-Vis spectroscopy. [17][18][19][20][21][22] At the first time, the functions of nonsubstituted polythiophene were restricted owing to its insolubility in water and water miscible solvents, as well as medium electrical conductivity. Solubility in water-miscible solvents and aqueous environment supports the formulation of the composites of polymers with noble-metal nanoparticles, which display the influence of local enhancement of electromagnetic field and the ability to make thin films.…”
Section: Introductionmentioning
confidence: 99%